Failure analysis based on microvoids damage model for DP600 steel on in-situ tensile tests. (March 2016) - Zhao, P.J.; Chen, Z.H.; Dong, C.F.
Abstract: Considering the effect of shear loading, an original GTN damage model is extended by combining the damage mechanics concept and the porous plasticity model. The extended model in terms of various stress triaxiality was deduced in detail. The model is extended by coupling two damage parameters into the yield function. The implementation is achieved by the development of the user material subroutine. Internal damage evolution was observed by scanning electron microscopy (SEM). Parameters were determined from experimental data and previous studies. The damage model was applied to in-situ tensile tests to compare its predictability in various specimens. The obtained numerical results were in good agreement with experimental results, showing better ductile fracture predictions.